2019
DOI: 10.1002/pon.5063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a web‐based reproductive health training program: ENRICH (Educating Nurses about Reproductive Issues in Cancer Healthcare)

Abstract: Objective: Educating Nurses about Reproductive Issues in Cancer Healthcare (ENRICH) is a web-based training program to assist oncology nurses with timely communication and relevant information regarding reproductive health issues (eg, risk of infertility, fertility preservation, and sexual health) to adolescent and young adult (AYA) patients and survivors. This manuscript describes impact on knowledge, perceived communication skills, and practice behaviors. Methods: The eight-module course incorporated didacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 17 publications
0
68
0
8
Order By: Relevance
“…Nineteen studies which evaluated an online CST intervention were identified 15,33‐50 . Extracted data are presented in Data S2.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies which evaluated an online CST intervention were identified 15,33‐50 . Extracted data are presented in Data S2.…”
Section: Resultsmentioning
confidence: 99%
“…Educational interventions for oncology providers have demonstrated improvement in provider‐reported knowledge and practice, but the impact on patient‐reported outcomes has not been routinely evaluated 58 . The Educating Nurses about Reproductive Issues in Cancer Healthcare (ENRICH) has demonstrated success in educating providers about sexual health among oncology patients 59 . Sexual communication models, including PLISSIT (Permission, Limited Information, Specific Suggestions, and Intensive Therapy) 60,61 can be helpful for providers to initiate sexual health discussions with patients.…”
Section: Discussionmentioning
confidence: 99%
“…58 The Educating Nurses about Reproductive Issues in Cancer Healthcare (ENRICH) has demonstrated success in educating providers about sexual health among oncology patients. 59 Sexual communication models, including PLISSIT (Permission, Limited Information, Specific Suggestions, and Intensive Therapy) 60,61 can be helpful for providers to initiate sexual health discussions with patients. The incorporation of a sexual health clinic within the oncology setting has been successful among adults with cancer 62 and may serve as a model for AYA cancer survivors in some settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, while patients claim for clear information, honesty, emotional support, and respect (Ussher et al, 2018 ), healthcare providers should have access to adequate training programs. Some experiences demonstrated that nurses' knowledge of reproductive issues, communication skills, and practice behaviors increased significantly after structured courses (Quinn et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%